Exclusive breastfeeding practices among women in formal employment in selected organizations in Kisumu Central Sub-County, Kisumu County, Kenya - Nyamiel, Felix M.; Muchiri, Joseph; Butto, Dennis (International Journal Of Community Medicine And Public Health, 2025)
Background: Encouraging exclusive breastfeeding among working women in metropolitan areas is a multifaceted issue. Comprehending the various facets associated with this and their impact on employed mothers’ decisions on exclusive nursing may facilitate the development of tactics to assist mothers in maintaining exclusive breastfeeding. This study investigated exclusive breastfeeding (EBF) practices among women in formal employment in Kisumu Central Sub-County, Kisumu County, Kenya. Methods: A descriptive cross-sectional design was employed, targeting 92 mothers with infants under 12 months working in selected public and private organizations. Stratified random sampling was used to select organizations, and data were collected via structured questionnaires. Ethical approvals were obtained, ensuring informed consent and confidentiality. Data were analyzed using statistical package for social sciences (SPSS) version 26, employing descriptive statistics and inferential statistics (Chi-square tests and logistic regression) to assess variable relationships. Statistical significance was set at p<0.05. Results: Breastfeeding policy (χ²(1)=4.50, p=0.034), nursing breaks (χ²(1)=6.25, p=0.012), employer encouragement (χ²(1)=5.76, p=0.016), and co-worker support (χ²(1)=4.00, p=0.046) showed significant relationships (p<0.05), revealing these factors as strong predictors of EBF practice. Schedule flexibility (χ²(1)=3.84, p=0.050) was borderline significant, while daycare availability (χ²(1)=2.25, p=0.134) did not show a significant association. Conclusions: The study concluded that organizational culture has an influence on exclusive breastfeeding practices among employed mothers. Gaps in workplace infrastructure, including the lack of daycare facilities and inflexible schedules, were identified as notable barriers. The study recommended enhanced collaboration between the government and employers to promote EBF among working mothers.